Pendidikan Islam dalam Perspektif Syed Naquib Al-Attas dan Relevansinya bagi Pengembangan Pendidikan Islam di Indonesia - Mohammad David El Hakim; Eni Fariyatul Fahyuni (Pendidikan Agama Islam STIT Palapa Nusantara, 2020)
This study aims to determine the concept of Islamic education in the perspective of Syed Muhammad Naquib al-Attas and its relevance for the development of Islamic education in Indonesia. This study is a library research with a qualitative approach. The data collection method used is the method of documentation through systematic and holistic data collection. Then the data is analyzed descriptively and critically. The results of this study are the findings that: (1) Syed Muhammad Naquib al-Attas is a highly educated religious figure. This is evidenced by his educational background from childhood to adulthood which is not far from the intellectual field despite having been involved in the military world. He delivered hundreds of scientific speeches in various countries in the world, especially in Islamic countries. He has won various national and international awards for his total contributions to contemporary Islamic thought. (2) The concept of Islamic education in the perspective of Syed Muhammad Naquib al-Attas can be seen holistically through his various ideas about humans as well as about the Islamization of science and standardization of basic understandings of Islamic terms. The most important idea in the concept of Islamic education according to him is reflected in the term ta'dib which refers to the meaning of Islamic education. (3) From the concept of Islamic education in the perspective of Syed Muhammad Naquib al-Attas there is relevance for the development of Islamic education in Indonesia. Among them is the concept of human beings who apparently also reflects the goal of national education, which is to develop the potential of students to become human beings who believe and fear God Almighty, noble, healthy, knowledgeable, capable, creative, independent, and become citizens which is democratic and responsible as written in Law No. 20 of 2003 concerning the National Education System.